PENGARUH ERITROPOETIN TERHADAP TINGKAT KEBERHASILAN TERAPI ANEMIA PADA PASIEN ANEMIA PADA PASIEN CHRONIC KIDNEY DISEASE DI RSUD ULIN BANJARMASIN - Wahyunita, Sari; Kurniawan, Guntur; Maharani, Sonia (Jurnal Insan Farmasi Indonesia, 2023)
Chronic kidney disease (CKD) is kidney damage for more than 3 months. The medicalÂ  in hospitalÂ  taken was hemodialysis. The aim of this study was to determine the success rate of anemia therapy, the incidence of anemia in CKD patients, and determine the effect of erythropoietin administration on the success rate of anemia therapy in CKD patients at Ulin Hospital, Banjarmasin. This research is a non-experimental research, observational in nature. Data collection was carried out prospectively. The sample used in this study was patient hemoglobin data in medical records that met the inclusion and exclusion criteria. The sample selection method used was total sampling. The measurement of therapeutic success used is the patient's hemoglobin data after being given erythropoietin. The research data obtained is displayed descriptively analytically. The research results of 90 patients with CKD (Chronic Kidney Disease). The results obtained were that 50 patients (55.55%) achieved success in anemia therapy and 40 patients (45.45%) did not achieve success in anemia therapy. The incidence of anemia was 90 patients (100%). Based on the analysis of data obtained, there is an influence of erythropoietin on the success of anemia therapy in Chronic Kidney Disease (CKD) at Ulin Regional Hospital, Banjarmasin.